Synthesis and characterization of empty fruit bunch cellulose-based coag-flocculant in removing turbidity for water treatment - Mohtar, Safia Syazana (2016)
The increasing demand for environmentally friendly technology for drinking water treatment process has recently gained considerable attention, especially, towards application of natural-based coagulants and flocculants (coag-flocculants). Abundance of oil palm empty fruit bunch (OPEFB) generated throughout the years gives potential for this biomass to be used as a cellulose source for coag-flocculant synthesis which has so far not been studied. Thus, this study focused on the extraction of cellulose from the OPEFB using ionic liquid dissolution-alkaline treatment technique and modification of the extracted cellulose into sulphonated cellulose (s-EFBC) and quaternized cellulose (q-EFBC). The performance evaluation of cellulose-based coag-flocculant in removing turbidity of the kaolin suspension solution and river water towards drinking water treatment application was carried out using a jar test method at various experimental conditions such as the molar ratio of reactants to anhydroglucose unit of cellulose, dosage, pH, kaolin concentration and sedimentation time. The characterization results show that the physico-chemical and spectral properties of the cellulose-based coag-flocculants were greatly influenced by the modification method used. It was found that a q-EFBC9 has the highest removal of turbidity (99.11±0.11%) exceeding the alum (97.79±0.54%). Optimization results gave the overall optimum responses of interest which were turbidity removal efficiency and sludge volume index at 62.5 mg/L of coag-flocculant dosage, pH 7 and 1400 mg/L kaolin concentration. The optimum dosage was found to deliver good performance in river water, in which, encouraging results were obtained from water quality tests. The coag-flocculation kinetics was studied at various initial coag-flocculant dosages. It was found that the highest dosage of 112.5 mg/L q- EFBC resulted in the highest adsorption capacity with the highest pseudo-second order rate constant (k2), initial adsorption rate (h) and film diffusion rate (Df). Meanwhile, the pseudo-first order constant, shear rate and collision rate coefficient of 62.5 mg/L q-EFBC9 for flocculation kinetics were found to be the highest. The adsorption capacity of river water was lower than that of kaolin suspension at the same dosage, resulted in lower k2, h and Df, and similar results were found in the parameters of the flocculation kinetics study. The dewatering study showed that the coag-flocculation process with 62.5 mg/L q-EFBC resulted in the lowest specific resistance to filtration and time to filter. The OPEFB cellulose has therefore shown a good potential to be converted into coag-flocculant for drinking water treatment as well as overcoming the oil palm plantation waste disposal problems.